The National Climate Change (Climate Change Mechanisms) Regulations, 2025 : S. I. no. 9 of 2025 - Uganda government (Kampala : LDC, 2025)
"This groundbreaking book collects contributions from many of the world's leading climate and energy law scholars and provides the first major study of national climate change acts. This cutting-edge type of legislation originated with the first Climate Change Act framework which was passed in the United Kingdom in 2008, and is intended to enable the law to grapple effectively with one of the great problems of our times, anthropogenic climate change. Since 2008, national framework climate legislation has been slowly but steadily emerging in countries across the world. This trailblazing collection employs a comparative analytical legal methodology and offers the first comprehensive study of this new, innovative form of legislative regime. In addition to containing broad internationalist chapters, deep-dive national case study chapters are included that focus on individual countries and provide analytical depth. A final chapter draws together the threads of the book's foregoing contributions to deduce generalisable conceptual insights based on current knowledge and experience. Uniquely, the book provides a conceptual model for climate change acts that can usefully inform the development of national framework climate legislation in all countries"--
Keywords: Climatic changes -- Law and legislation; Environmental law